The Validity of Fines Imposed as a Sanction by Regional Governments to Control Compliance With Covid-19 Health Guidelines - Airlangga, Bayu; Wijoyo, Suparto; Soekarwo, Soekarwo (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
As an effort to deal with the Covid-19 pandemic, the Government issued Presidential Instruction Number 6 of 2020 concerning Increasing Discipline and Law Enforcement of health Protocols in the Prevention and Control of Corona Virus Disease 2019 (Covid-19). In Presidential Instruction 6/2020 Regioal Heads are instructed to make Regional Head Regulations (Perkada) which contain sanctions for violation of obligations contained in the health protocol. Reffering to Law Number 12 of 2011 concerning Fomation of Legislation, Regional Head Regulations are not included in the hierarchy of statutory regulations. So this study discusses the validity of administrative sanctions in the form of fines contained in the Regional Head Regulation. Keywords: Administrative Fines, Regional Head Regulations, Covid-19.